The molecular basis of odor coding in the Drosophila larva. - Kreher, S.A.; Kwon, J.Y.; Carlson, J.R. (Neuron, 2005)
We have analyzed the molecular basis of odor coding in the Drosophila larva. A subset of Or genes is found to be expressed in larval olfactory receptor neurons (ORNs). Using an in vivo expression system and electrophysiology, we demonstrate that these genes encode functional odor receptors and determine their response spectra with 27 odors. The receptors vary in their breadth of tuning, exhibit both excitation and inhibition, and show different onset and termination kinetics. An individual receptor appears to transmit signals via a single ORN to a single glomerulus in the larval antennal lobe. We provide a spatial map of odor information in the larval brain and find that ORNs with related functional specificity map to related spatial positions. The results show how one family of receptors underlies odor coding in two markedly different olfactory systems; they also provide a molecular mechanism to explain longstanding observations of larval odor discrimination.